Contrast-enhanced harmonic EUS with novel ultrasonographic contrast (Sonazoid) in the preoperative T-staging for pancreaticobiliary malignancies - Imazu, H.; Uchiyama, Y.; Matsunaga, K.; Ikeda, Kei-Ichi; Kakutani, H.; Sasaki, Y.; Sumiyama, K.; Ang, T.L.; Omar, S.; Tajiri, H. (Informa Healthcare, 2010)
Objective. Sonazoid is a new second-generation microbubble contrast for ultrasonography. In this pilot study, the diagnostic role of contrast-enhanced harmonic imaging endoscopic ultrasonography (CH-EUS) with Sonazoid was prospectively evaluated in preoperative T-staging of pancreaticobiliary malignancies. Patients and methods. Patients with suspected pancreaticobiliary malignancies underwent CH-EUS by a single examiner. After the lesions were observed carefully with conventional harmonic imaging EUS (H-EUS), CH-EUS was performed with intravenous injection of Sonazoid. A reviewer who was blinded reviewed the recordings of H-EUS and CH-EUS and assessed the T-staging. The accuracy of H-EUS and CH-EUS for T-staging was compared to the results of surgical histopathology in patients who underwent surgery. Result. Twenty-six patients underwent surgical resection and could be included in the study. The final diagnosis were pancreatic cancer in 11, bile duct cancer in 7, gallbladder cancer in 4 and ampullary cancer in 4. The overall accuracy of H-EUS and CH-EUS for T-staging were 69.2 (18/26) and 92.4% (24/26), respectively (p < 0.05). There were disagreement in six cases between H-EUS and CH-EUS. CH-EUS staged correctly in all of these six cases, whereas H-EUS misdiagnosed the depth of invasion in one case of gallbladder cancer and one case of ampullary cancer, and invasion of portal vein in two cases of pancreatic cancer and two cases of bile duct cancer. Conclusion. The depth of invasion of biliary cancer and vascular invasion of pancreatic and biliary cancer could be demonstrated more clearly with CH-EUS compared to H-EUS. CH-EUS has the potential to improve the diagnostic accuracy of preoperative T-staging of pancreaticobiliary malignancies.